2015
DOI: 10.1590/1676-06032014000814
|View full text |Cite
|
Sign up to set email alerts
|

Non-volant mammals from Núcleo Santa Virgínia, Serra do Mar State Park, São Paulo, Brazil

Abstract: This study presents data on the composition and species richness of non-flying mammals in the northern part of the Parque Estadual da Serra do Mar, called Nú cleo Santa Virgínia (NSV -around 17000 hectares of Atlantic Forest), Sã o Paulo state, southeastern Brazil. The species list was based on ca. 660 km of line-transects, 25512 hours of cameras traps, 7740 trap.nights for small mammals, and 394 track-station.days, as well as occasional records and registers from local people (period 2002 to 2009 Introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…These results are quite surprising and indicate that three individuals are at least temporarily using the SVU (Figure 2). The presence of this large carnivore highlights the importance of this conservation unit and that it maintains a high degree of habitat integrity, with its high species diversity (Ripple et al 2014, Rocha-Mendes et al 2015. Moreover, this fact likely ensures more stability to this ecosystem since the jaguar has an important role on a top-to-down population control (Terborgh et al 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are quite surprising and indicate that three individuals are at least temporarily using the SVU (Figure 2). The presence of this large carnivore highlights the importance of this conservation unit and that it maintains a high degree of habitat integrity, with its high species diversity (Ripple et al 2014, Rocha-Mendes et al 2015. Moreover, this fact likely ensures more stability to this ecosystem since the jaguar has an important role on a top-to-down population control (Terborgh et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Because of its large size, the park was divided into ten administrative units, which include the Santa Virginia unit, where the study was conducted and which is recognized for its high biodiversity (Galetti et al 2009, Rocha-Mendes et al 2015. However, although the jaguar is believed to occur there (Rocha-Mendes et al 2015), its presence has not been confirmed, after extensive camera trapping efforts between the years 2008-2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although similar in many ecological aspects, these three sites differ in the abundance of large mammals that may interfere in the diet of small mammals [ 37 ]. At least 25 species, nine marsupials and 16 small rodents, compose the small mammal communities of this region [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Para esse fim, o armadilhamento fotográfico (camera-trap) foi utilizado como método principal, e de forma complementar, foram utilizados dados de visualizações ocasionais e registros indiretos (e.g., pegadas, fezes, tocas e vocalizações). A combinação desses métodos resulta em um melhor resultado no registro da riqueza de espécies (Brocardo et al 2013, Rocha-Mendes et al 2015 Preto e a garagem de uma concessionária localizada em frente a essa base, para captura de pequenos roedores exóticos (coordenadas: 25°37'40,13" S, 54°27'46,64" O; cerca de 2 km da área amostrada pelas transecções lineares). Na FOM, durante pesquisa sobre interação da fauna de pequenos mamíferos com sementes de Araucaria angustifolia foram estabelecidas seis grades amostrais, monitoradas no período de maio a agosto de 2012 e de outubro de 2012 a janeiro de 2013 (Ferracioli 2013).…”
Section: Coleta De Dadosunclassified